Patient-derived lung cancer organoids as in vitro cancer models for therapeutic screening - Minsuh Kim; Hyemin Mun; Chang Oak Sung; Eun Jeong Cho; Hye-Joon Jeon; Sung-Min Chun; Da Jung Jung; Tae Hoon Shin; Gi Seok Jeong; Dong Kwan Kim; Eun Kyung Choi; Seong-Yun Jeong; et al. (Nature Communications, 2019)
The clinical efficacy of standard therapy in lung cancer is limited by high level of heterogeneity. Here, the authors report patient-derived lung cancer organoids from different histological subtypes and show them to faithfully recapitulate the histology, genomics, and drug responses of the primary lung tumours.